Pengaruh Literasi Pajak, Modernisasi Sistem Administrasi, Insentif Pajak dan Moral Pajak Terhadap Kepatuhan Wajib Pajak UMKM - Dwi Rahmawati Kusumadewi; Dyarini Dyarini (Jurnal Akuntansi dan Keuangan, 2022)
This study discusses taxpayer compliance, one of which is in a sector that has considerable potential as part of tax revenue but is not yet at the expected level of tax compliance, namely MSME taxpayers. This study aims to determine the effect of tax literacy, administrative system modernization, tax incentives, and tax morale on MSME taxpayer compliance. The research method used is a quantitative approach with a survey method. Respondents in this study were MSME taxpayers in South Tangerang City, with a total sample of 100 respondents. The data analysis method used is multiple linear regression, with a data processing tool in the form of SPSS. The results partially show that tax literacy has no effect on MSME taxpayer compliance, modernization of the administrative system affects MSME taxpayer compliance, tax incentives affect MSME taxpayer compliance, and tax morale affects MSME taxpayer compliance. The results of the study simultaneously show that tax literacy, administrative system modernization, tax incentives, and tax morale affect MSME taxpayer compliance. The implications of this finding are expected to be involved as one of the considerations for the Directorate General of Taxes, by knowing the factors related to taxpayer compliance, especially in this case MSME taxpayers, so that they can contribute as a basis for decision making or making tax policies and regulations in an effort to increase tax revenue. with tax compliance in Indonesia. Keywords : tax literacy, administrative system modernization, tax incentives,tax morale, taxpayer compliance